Left Ventricular End-Systolic Volume Is a Reliable Predictor of New-Onset Heart Failure with Preserved Left Ventricular Ejection Fraction. (29th June 2020) - Kato, Marina; Kitada, Shuichi; Kawada, Yu; Nakasuka, Kosuke; Kikuchi, Shohei; Seo, Yoshihiro; Ohte, Nobuyuki
Abstract : Background . Left ventricular (LV) ejection fraction (EF) and LV volumes were reported to have prognostic efficacy in cardiac diseases. In particular, the end-systolic volume index (LVESVI) has been featured as the most reliable prognostic indicator. However, such efficacy in patients with LVEF ≥ 50% has not been elucidated. Methods . We screened the patients who received cardiac catheterization to evaluate coronary artery disease concomitantly with both left ventriculography and LV pressure recording using a catheter-tipped micromanometer and finally enrolled 355 patients with LVEF ≥ 50% and no history of heart failure (HF) after exclusion of the patients with severe coronary artery stenosis requiring early revascularization. Cardiovascular death or hospitalization for HF was defined as adverse events. The prognostic value of LVESVI was investigated using a Cox proportional hazards model. Results . A univariable analysis demonstrated that age, log BNP level, tau, peak − d P /d t, LVEF, LV end-diastolic volume index (LVEDVI), and LVESVI were associated with adverse events. A correlation analysis revealed that LVESVI was significantly associated with log BNP level ( r = 0.356, p < 0.001 ), +d P /d t ( r = −0.324, p < 0.001 ), −d P /d t ( r = 0.391, p < 0.001 ), and tau ( r = 0.337, p < 0.001 ). Multivariable analysis with a stepwise procedure using the variables with statistical significance in the univariable analysis revealed that aging, an increase in BNP level, and enlargement of LVESVI were significant prognostic indicators (age: HR: 1.071, 95% CI: 1.009–1.137, p = 0.024 ; log BNP : HR : 1.533, 95% CI: 1.090–2.156, p = 0.014 ; LVESVI : HR : 1.051, 95% CI: 1.011–1.093, p = 0.013, respectively). According to the receiver-operating characteristic curve analysis for adverse events, log BNP level of 3.23 pg/ml (BNP level: 25.3 pg/ml) and an LVESVI of 24.1 ml/m 2 were optimal cutoff values (BNP : AUC : 0.753, p < 0.001, LVESVI : AUC : 0.729, p < 0.001, respectively). Conclusion . In patients with LVEF ≥ 50%, an increased LVESVI is related to the adverse events. LV contractile performance even in the range of preserved LVEF should be considered as a role of a prognostic indicator.